Teori Pendidikan Multikultural dan Pendekatan Pendidikan Multikultural - Husnul Pathonah; Wardina (CV Putra Publisher, 2023)
Multicultural education in this study is something that has a process of developing all of its potential where every problem that occurs in society will cause conflict. As a consequence of the diversity of culture, ethnicity, ethnicity and sect (religion). Multicultural education is often related to diversity which respects each other and lives together without distinguishing differences in terms of ethnicity, language, ethnicity and religion. Multicultural education originally from various views and ideas that emerged. There are many influences from very rapid global developments in the lives of people who are experiencing change. What is the value of awareness of the meaning of learning about multicultural education which is based on a principle and the concept of multiculturalism, namely a concept that recognizes diversity, accepts differences be it gender, race, and religion based on values ​​and democratic understanding that builds the nation so that it is united. Which is very relevant to use today so as not to leave its cultural roots through multicultural education.